Inorganic nanoparticles : synthesis, applications, and perspectives - Altavilla, Claudia; Ciliberto, E. (Enrico) (FL : CRC Press, 2011)
"Among the various nanomaterials, inorganic nanoparticles assume a special place because they are cheaper than others and easier to synthesize in the laboratory and mass produce. This text captures the current advances and fundamentals of synthesis, characterization, and application development of these materials. Topics discussed include magnetic materials, oxide thin films, solid state lighting, semiconductor nanoparticles for light emitting devices, solar energy, energy storage devices, and quantum dots in biomedicine. Highlighting the vast scope of applications, the book features contributions from an array of experts at the top of their fields"--Provided by publisher.
Inorganic nanoparticles : synthesis, applications, and perspectives : an overview / Claudia Altavilla and Enrico Ciliberto -- Inorganic nanoparticles for the conservation of works of art / Piero Baglioni and Rodorico Giorgi -- Magnetic nanoparticle for information storage applications / Natalie A. Frey and Shouheng Sun -- Inorganic nanoparticles gas sensors / B.R. Mehta, V.N. Singh, and Manika Khanuja -- Light-emitting devices based on direct band gap semiconductor nanoparticles / Ekaterina Neshataeva, Tilmar Kümmell, and Gerd Bacher -- Formation of nanosized aluminum and its applications in condensed phase reactions / Jan A. Puszynski and Lori J. Groven -- Nanoparticles for fuel cell applications / Jin Luo ... [et al.] -- Inorganic nanoparticles for photovoltaic applications / Elif Arici -- Inorganic nanoparticles and rechargeable batteries / Doron Aurbach and Ortal Haik -- Quantum dots designed for biomedical applications / Andrea Ragusa ... [et al.] -- Magnetic nanoparticles for drug delivery / Claudia Altavilla -- Nanoparticle thermotherapy : a new approach in cancer therapy / Joerg Lehmann and Brita Lehmann -- Inorganic particles against reactive oxygen species for sun protective products / Wilson A. Lee and Miriam Raifailovich -- Innovation inorganic nanoparticles with antibacterial properties attached to textiles by sonochemistry / Nina Perkas ... [et al.] -- Inorganic nanoparticles for environmental remediation / Thomas B. Scott -- Inorganic nanotubes and fullerene-like structures : from synthesis to applications / Maya Bar-Sadan and Reshef Tenne -- Inorganic nanoparticles for catalysis / Naoki Toshima -- Nanocatalysts : a new "dimension" for nanoparticles? / Paolo Ciambelli, Diana Sannino, and Maria Sarno.
Includes bibliographical references and index.
Keywords: Nanoparticles